1999
DOI: 10.1002/(sici)1096-9098(199909)72:1<50::aid-jso14>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Total vascular exclusion for liver resections: Pros and cons

Abstract: Dramatic improvements in morbidity and mortality rates following liver resections have been reported in the past decade. Consequently, the indications for hepatectomy are becoming more liberal. Many techniques of liver resection with or without vascular clamping have been reported with excellent clinical results. Total vascular exclusion (TVE) of the liver during parenchymal transection has been advocated susceptible to increase the resectability of tumors that might not be safely approached by other technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Habib et al [29] reported a 39 % postoperative morbidity rate in 56 liver resections with complete hepatic vascular exclusion in non-cirrhotic patients. Extensive mobilization of the liver including suprahepatic IVC could predispose to formation of postoperative subphrenic fluid collections and pleural effusions [16]. Thus, despite the high number of patients with complex resections, including a significant cirrhotic population, our overall morbidity and mortality rates are consistent with reported data.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Habib et al [29] reported a 39 % postoperative morbidity rate in 56 liver resections with complete hepatic vascular exclusion in non-cirrhotic patients. Extensive mobilization of the liver including suprahepatic IVC could predispose to formation of postoperative subphrenic fluid collections and pleural effusions [16]. Thus, despite the high number of patients with complex resections, including a significant cirrhotic population, our overall morbidity and mortality rates are consistent with reported data.…”
Section: Discussionsupporting
confidence: 86%
“…TVE offers the advantage of combining total vascular inflow and outflow occlusion of the liver, thus isolating it completely from the systematic circulation. This approach can decrease intraoperative blood loss and increase the resectability of centrally or posteriorly located tumors close to the major hepatic veins or the IVC [15][16][17]. The benefits of TVE, however, are tempered by the impact of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The development of living donor liver transplantation (LDLT) in Korea has contributed to the reciprocal advancement in aggressive hepatobiliary surgeries, especially regarding vascular reconstruction of the IVC and portal vein [ 1 ]. Clamping of the IVC such as total hepatic vascular exclusion (THVE) is not frequently performed during hepatobiliary surgery [ 2 - 7 ]. However, it is an essential procedure for liver transplantation.…”
Section: Introductionmentioning
confidence: 99%